2018
DOI: 10.1007/s11606-018-4579-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender Pay Gaps in Medicine: Moving from Explanations to Action

Abstract: A lmost one half of medical school students are now women, and women make up over one third of the total physician workforce. Yet gender inequities in physician compensation persist, with reported gender-based pay gaps of 16 to 37%.1 Many potential explanations for this pay gap have been suggested, including prioritization of work-life balance, rates of working part-time, specialty choice, years of experience, fewer women in leadership roles and in senior positions, and lack of mentorship and sponsorship for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Our results corroborate previous findings highlighting the gender salary gap within dermatology ( Roy, 2018 , Weeks and Wallace, 2007 ). However, there appears to be a trend toward closing this gap: The overall median salary for women over this 5-year period increased by almost 20% but only increased by around 9% for men.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate previous findings highlighting the gender salary gap within dermatology ( Roy, 2018 , Weeks and Wallace, 2007 ). However, there appears to be a trend toward closing this gap: The overall median salary for women over this 5-year period increased by almost 20% but only increased by around 9% for men.…”
supporting
confidence: 92%
“…Gender disparity in salary and representation is a major ongoing issue in academic medicine ( Roy, 2018 , Weeks and Wallace, 2007 ). Although women composed almost half (47.9%) of dermatologists in Canada and the United States in 2018, they earned a 28% lower median salary than men, and only 26.1% of chiefs/chairs were women ( Shah et al, 2018 , Weeks and Wallace, 2007 ).…”
mentioning
confidence: 99%
“…Numerous studies, mostly from the United States and the United Kingdom, have shown a clear gender pay gap among phys icians. [7][8][9][10][11][12][13] This effect is seen in clinical, 14 research 15 and aca demic 16,17 environments. Inequities start at the early stages of a medical career, 18,19 deepen with time, 20 continue into retire ment 21 and affect lifetime wealth, 22 with estimates as high as $2.5 million over a 30year career.…”
Section: Is the Gender Pay Gap Real?mentioning
confidence: 94%
“…Our results are comparable to those of similar studies that have evaluated physician salaries in multiple jurisdictions. [2][3][4][5][6][28][29][30] Studies evaluating specific subgroups of physicians have found sex-and gender-based salary discrepancies among research, academic and clinical physician groups. 2,7,9,31,32 Similar to our findings, previous studies found that female physicians earned less than male physicians at the start of their careers, and that the income difference grew with time.…”
Section: Discussionmentioning
confidence: 99%